EVALUASI TUGAS CAMAT DALAM MELAKUKAN PEMBINAAN PEMERINTAHAN DESA DI KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HILIR - Nurhalimah, Siti; Nurmasari, Nurmasari; Zulkifli, Zulkifli (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2022)
The research objective was to determine the results of the camat's assignment in fostering village governance in Lubuk Batu Jaya Subdistrict, Indragiri Hulu Regency. This is to find out the obstacles to the task of the sub-district head in fostering village governance in Lubuk Batu Jaya Subdistrict, Indragiri Hulu Regency. This type of descriptive research uses a quantitative approach with a population of 23 people, community leaders, village heads and camat office employees. Data collection was carried out by means of interviews, questionnaires, documentation and observation, all data collected were grouped by type and analyzed descriptively and conclusions could be drawn from the research results. Based on the results of the study, it was found that the evaluation of the sub-district head's duties in conducting Village Government Development in Lubuk Batu Jaya District, Indragiri Hulu Regency was in the quite good category, due to the five research indicators, namely providing guidance, giving direction, providing education and training, giving instructions and literature or the manual has been implemented. The inhibiting factor for the guidance carried out by the sub-district head to the village government is that the guidance carried out by the sub-district head has not been carried out routinely, the direction is given to the sub-district head only if the village apparatus experiences problems in the work process, and the sub-district head does not provide education and training every month, the sub-district head only provides guidance if he receives a report. village government task constraints.